Exploring the implementation of an evidence-based health promotion intervention for women experiencing intimate partner violence (iHEAL) in diverse contexts: Study Protocol - Marilyn Ford-Gilboe; Kelly Scott-Storey; Annette J. Browne; Colleen Varcoe; Caitlin Burd; Karen Campbell; Christine Garinger; Susan Jack; Kelsey Lynch; Jeannie Malcolm; Tara Mantler; Sue O’Donnell; et al. (PLoS ONE, 2025)
Objectives This participatory, mixed methods study will explore how iHEAL, a woman-led, nurse-delivered health promotion intervention for women who have experienced intimate partner violence (IPV), can be implemented in real-world, community-based health care settings located in 3 Canadian provinces. Grounded in the Active Implementation Frameworks, the study’s primary aim is to identify the processes, resources and supports necessary to implement and sustain this novel program with fidelity while maintaining its benefits for women. Methods/Design Over 2.5 years, each organization will plan for and deliver the iHEAL program, supported by an iHEAL Consultant. To explore implementation processes and fidelity, successes and challenges, and any value-added of iHEAL to organizations and/or communities, qualitative interviews will be conducted with 3 groups of participants: 1) organizational leaders; 2) implementation/delivery team members (nurses and supervisors); and 3) external stakeholders or agencies supporting iHEAL through referrals or other collaboration. High level notes capturing key issues and decisions at planning meetings will supplement these data. Administrative program data will be collected to assess program reach, participant engagement, and aspects of fidelity. Women participating in iHEAL will also be invited to complete pre/post intervention surveys to assess changes in key outcomes, with a subsample of 60 women to be interviewed about their experiences of iHEAL and suggestions for strengthening the program. Qualitative data will be analyzed using Rapid Team Based Qualitative Analysis and Reflective Thematic Analysis. Quantitative data will be summarized using descriptive statistics; pre-post intervention changes in outcomes collected in women’s surveys will be analyzed using paired t-tests. Ethical approval has been obtained, and all participants will provide informed consent. Significance The findings of this research are expected to yield insights about organizational factors that shape the delivery of iHEAL and support the development of guidance materials for future iHEAL implementation and scale up.